2012
DOI: 10.1007/s13349-011-0015-7
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effect on vibration properties of civil structures: a literature review and case studies

Abstract: Changing environmental conditions, especially temperature, have been observed to be a complicated factor affecting vibration properties, such as frequencies, mode shapes, and damping, of civil structures. This paper reviews technical literature concerning variations in vibration properties of civil structures under changing temperature conditions. Most of these studies focus on variations in frequencies of bridge structures, with some studies on variations in mode shapes and damping and other types of structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
146
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(150 citation statements)
references
References 43 publications
2
146
0
2
Order By: Relevance
“…Most problematic of such variables is temperature [89], with many techniques having been developed over the years dedicated to estimating and mitigating its influence; generally through various data normalisation techniques, see Sohn [90] and Xia et al [96]. The present section details techniques that can be employed when environmental and operational data is available (regression models) and when it is not (pattern recognition).…”
Section: Advancements To Environmental and Operational Challengesmentioning
confidence: 99%
“…Most problematic of such variables is temperature [89], with many techniques having been developed over the years dedicated to estimating and mitigating its influence; generally through various data normalisation techniques, see Sohn [90] and Xia et al [96]. The present section details techniques that can be employed when environmental and operational data is available (regression models) and when it is not (pattern recognition).…”
Section: Advancements To Environmental and Operational Challengesmentioning
confidence: 99%
“…For example, while the elastic modulus of concrete generally varies with temperature, humidity and age [9], these variations are seldom taken into account in a PB model and in turn, affect the reliability of the St-Id process. Incorporating effects of ambient conditions, which are now recognized to significantly affect structural behaviour, in PB models is also difficult [10], [11]. Therefore robust approaches for measurement interpretation that are generic and readily applicable without requiring detailed a priori knowledge of structures have tremendous value in the context of extracting information from monitoring for bridge management.…”
Section: Introductionmentioning
confidence: 99%
“…Rather fewer studies have examined the link between thermal loads (diurnal and seasonal temperature variations) and dynamic properties, which are reviewed by Xia, Chen, Weng, Ni and Xu (2012). Of these only a few studies have reported such links in suspension bridges (Oh et al, 2009;Miao et al, 2011;Ding & Li, 2011).…”
Section: Introduction: Variations In Bridge Loading and Dynamic Respomentioning
confidence: 99%